Effect of curcuma (Curcuma xanthorriza roxb) immersion on the survival of tilapia (Oreochromis niloticus) - Yayu Angriani Ngodu; Rully Tuiyo; Mulis Mulis (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the duration of soaking of curcuma (Curcuma xanthorriza roxb) powder on the survival of tilapia (Oreochromis niloticus) seeds infected with Aeromonas hydrophilla bacteria. This study was an experiment with a Completely Randomized Design (CRD) using analysis of variance (ANOVA) with four treatments and three repetitions. The treatments used were curcuma powder immersion, which were treatments A (3 minutes), B (5 minutes), C (7 minutes) and D (Control). The results showed that different soaking time using ginger powder did not affect the survival of tilapia seeds. The best treatment is treatment A (3 minutes) with a survival rate of 86.67%.